PENURUNAN KADAR KAFEIN DAN ASAM TOTAL PADA BIJI KOPI ROBUSTA MENGGUNAKAN TEKNOLOGI FERMENTASI ANAEROB FAKULTATIF DENGAN MIKROBA NOPKOR MZ-15 - Ana Farida; Evi Ristanti R; Andri Cahyo Kumoro (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2013)
Coffee is one of the most famous beverages in the world. Coffee favored because it has unique taste and flavor. However, coffee contains excess acid and caffeine which has negative impacts on health. Fermentation is one of the alternative methods to improve the quality of coffee beans. After fermentation process ,it is expected to produce coffee with low caffeine content and low organic acid, as well as great aroma and distinctive flavors. Raw material in this experiment is robusta coffee from Temanggung. The microbes is Nopkor MZ-15 and as a source of nutrients needed sprouts of green beans, tapioca starch and ZA fertilizer. Variables in this experiment are based on ZA fertilizer concentrations. These 1%,2% and 3% wZA/wcoffee (gr/gr). Fermentation processes will be held during 12-36 hours. Analysis of coffee beans as fermentation products which include caffeine, acid contents and water content are needed after fermentation process. These analyses can be done by quantitative and qualitative test. Quantitative tests include HPLC method for caffeine analysis, alkalimeter method and Qualitative test includes sensory method such as panel test is needed for flavor analysis. Based on research, resulted optimum time of fermentation is 18 hours and optimum ZA concentration is 2% w ZA/w coffee with caffeine ( 46,88 mg/100 ml) and pH (5,49).